Influence of thermal diffuse scattering on image contrast in scanning transmission electron microscopy - Croitoru, Marin (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2007)

(untitled)
We analyze the loss of contrast in simulated atomic-resolution annular dark-field scan-